EMI-resilient amplifier circuits - van der Horst, Marcel J. (Analog Circuits and Signal Processing, 2014)
This book enables circuit designers to reduce the errors introduced by the fundamental limitations and electromagnetic interference (EMI) in negative-feedback amplifiers.  The authors describe a systematic design approach for application specific negative-feedback amplifiers, with specified signal-to-error ratio (SER).  This approach enables designers to calculate noise, bandwidth, EMI, and the required bias parameters of the transistors used in  application specific amplifiers in order to meet the SER requirements.   ·         Describes design methods that incorporate electromagnetic interference (EMI) in the design of application specific negative-feedback amplifiers; ·         Provides designers with a structured methodology to avoid the use of trial and error in meeting signal-to-error ratio (SER) requirements; ·         Equips designers to increase EMI immunity of the amplifier itself, thus avoiding filtering at the input, reducing the number of components and avoiding detrimental effects on noise and stability.